Neurovascular and perfusion imaging findings in coronavirus disease 2019: Case report and literature review. Issue 5 (October 2020) - Soldatelli, Matheus Dorigatti; Amaral, Lázaro Faria do; Veiga, Viviane Cordeiro; Rojas, Salomón Soriano Ordinola; Omar, Samir; Marussi, Victor Hugo Rocha
Central nervous system involvement in severe acute respiratory syndrome caused by coronavirus disease 2019 (COVID-19) has increasingly been recognised in the literature, and possible mechanisms of neuroinvasion, neurotropism and neurovirulence have been described. Neurological signs have been described in 84% of COVID-19 intensive care unit patients, and haemostatic abnormalities in such patients may play an important role, with a broad spectrum of neuroimaging findings. This report describes the magnetic resonance imaging neurovascular findings in an acutely ill patient with COVID-19, including perfusion abnormalities depicted in the arterial spin labelling technique.